2022
DOI: 10.3390/biology11060882
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 Altered Rice VOCs Aggravate Population Occurrence of Brown Planthoppers by Improving Host Selection Ability

Abstract: It is predicted that plant volatile organic compounds (VOCs) are affected by the atmospheric CO2 levels rising globally, which further affects the interaction between plants and herbivorous insects, especially the host selection behavior of herbivorous insects. In this study, the effects of elevated CO2 on the host-selection behavior of the brown planthopper (BPH) Nilaparvata lugens, and the emission of VOCs from the healthy and BPH-damaged rice plants were studied simultaneously to make clear the population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(74 reference statements)
0
1
1
Order By: Relevance
“…In our study, the relative expression levels of LOC113203279 and LOC113205269 were not affected by all treatments, but the transcription level of LOC113214975 was up-regulated universally, and LOC113205302 was significantly down-regulated under all treatments. This indicated that the functions of LOC113214975 and LOC113205302 in olfactory recognition were conservative and critical, although they were different from what has previously been reported [ 29 , 57 , 58 ]. It was more likely that there may be antagonism between LOC113214975 and LOC113205302 .…”
Section: Discussioncontrasting
confidence: 84%
“…In our study, the relative expression levels of LOC113203279 and LOC113205269 were not affected by all treatments, but the transcription level of LOC113214975 was up-regulated universally, and LOC113205302 was significantly down-regulated under all treatments. This indicated that the functions of LOC113214975 and LOC113205302 in olfactory recognition were conservative and critical, although they were different from what has previously been reported [ 29 , 57 , 58 ]. It was more likely that there may be antagonism between LOC113214975 and LOC113205302 .…”
Section: Discussioncontrasting
confidence: 84%
“…In herbivorous insects, the main behaviours affecting fitness, such as feeding, mating, and oviposition, are influenced by plant‐related cues (Awmack & Leather, 2002; Carrasco et al, 2015; Städler et al, 2002; Wang et al, 2022). The success of an oligophagous herbivorous insect, in particular, depends on its ability to locate the best host plant, use its nutrients and cope with its defence (Bernays & Chapman, 1994; Fernandez & Hilker, 2007).…”
Section: Introductionmentioning
confidence: 99%